Soft computing models in industrial and environmental applications, 6th international conference SOCO 2011 - SOCO (Conference) 2011 Salamanca, Spain); Corchado, Emilio; Snášel, Václav; Sedano, Javier; Hassanien, Aboul Ella; Calvo, José Luis; Ślȩzak, Dominik (Berlin Heidelberg Springer, 2011)
This volume of Advances in Intelligent and Soft Computing contains accepted papers presented at SOCO 2011 held in the beautiful and historic city of Salamanca, Spain, April 2011. This volume presents the papers accepted for the 2011 edition, both for the main event and the Special Sessions. SOCO 2011 Special Sessions are a very useful tool in order to complement the regular program with new or emerging topics of particular interest to the participating community. Four special sessions were organized related to relevant topics as: Optimization and Control in Industry, Speech Processing and Soft Computing, Systems, Man & Cybernetics and Soft Computing for Medical Applications
Image analysis and processing -- Intelligent Systems.-Multi-agents and Ambient Intelligence -- classification and clustering methods -- Evolutionary Computation -- Applications -- Optimization and Control Systems in Industry.-Speech Processing & Compression: Soft computing models -- System, Man, & Cybernetics.-Soft Computing for Medical Applications
Includes bibliographical references and author index
Electronic reproduction
Keywords: Soft computing -- Congresses